L'évidence de l'égalité des sexes : une philosophie oubliée du XVIIe siècle - Dorlin, Elsa (Collection Bibliothèque du féminisme, 2000)
Au XVIIe siècle, quatre philosophes, à quelques décennies d'intervalle, formulent en des styles très différents la thèse selon laquelle l'égalité entre les hommes et les femmes est une évidence, une vérité indiscutable. Marie de Gournay, Anna Maria Van Schurman, François Poullain de la Barre et Gabrielle Suchon, estiment que si les interdictions et les discriminations frappant les femmes perdurent, c'est que la querelle entre les défenseurs et les pourfendeurs du " Beau Sexe " est biaisée : les présupposés de la différence sexuelle rendent la question de l'égalité ou de l'inégalité des sexes indécidable.
Keywords: 1600-1699; approches et analyses; cours; discipline; discours dominant; europe; fem1000; france; histoire des femmes*; histoire et politique; incontournable; inégalités; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme